Higher Education of MUI Cleric Cadres In North Sumatera 1980-2020 - Rambe, Syahril; Nasution, Hasan Bakti; Arsyad, Junaidi (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
The Indonesian Ulema Council (MUI) has established the Pendidikan Tinggi Kader Ulama (PKU), or Scholars Cadre Education Program, to train future ulama. This research aims to explore the dynamics and effectiveness of PKU programs in North Sumatra from 1980 to 2020, assessing their impact on producing capable scholars and evaluating their alignment with community expectations. A social historical approach is used to assess religious and social institutional elements relevant to the research theme. The study covers various aspects such as the objectives, curriculum, human resources, alumni, institutional management, and facilities of PTKU-MUI in North-Sumatra. The focus is on analyzing how the institution operates and develops in the social and educational context. The research results show that the PKU initiative is essential for ensuring the continuity of Islamic scholarship, addressing the shortage of knowledgeable scholars, and adapting to the evolving needs of the Muslim community.